The Role of Islamic Religious Counselors in Providing Premarital Guidance at the Religious Affairs Office of Sultan Daulat District, Subulussalam City, Aceh Province - Zainuddin; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (International Journal of Science and Society, 2024)
This study aims to analyze the implementation of premarital guidance at the Religious Affairs Office of Sultan Daulat District, the materials provided in premarital guidance at the Religious Affairs Office of Sultan Daulat District, and the SWOT analysis of premarital guidance at the Religious Affairs Office of Sultan Daulat District. The study used a nautical qualitative approach with data collection techniques in the form of observation, interviews and documentation studies. This study revealed several important findings regarding premarital guidance at the Religious Affairs Office of Sultan Daulat District. The implementation of this guidance follows the requirements for marriage registration in accordance with the latest regulations. Participants were very satisfied with the ease and flexibility of time provided during the guidance, which was arranged according to the agreement between the presenter and participants. Religious counselors showed responsibility and consistency in their duties, making positive contributions to the community by being active in discussions and question and answer sessions. The guidance material was delivered by two groups of presenters: Islamic religious counselors and representatives from the National Population and Family Planning Agency and health agencies. The material covered the management of psychology and family dynamics, reproductive health, and the foundations of a harmonious family. Religious counselors used an independent method in delivering their material. The SWOT analysis shows that religious counselors play a role in reducing the divorce rate in the area. They are also effective in reducing the spread of hoax news about premarital counseling. The guidance methods applied and the flexibility of implementation time help simplify the process and overcome the negative stigma that is often associated with premarital counseling at the Sultan Daulat Religious Affairs Office.